Control of Shear Dispersion by the Permeable Porous Wall of a Capillary Tube. Issue 11 (4th September 2020) - Kou, Zuhao; Dejam, Morteza
Abstract: The transfer of a neutral nonreacting mass species was studied in a capillary tube with a permeable porous wall, under the effect of combined pressure‐driven and electro‐osmotic flows or simply combined flows (CF). An exact expression for the shear dispersion coefficient in a tube under the influence of CF is derived, which remains constant when λ D, inversely propotional to the permeability of the porous medium, is smaller than 1 or larger than 100 for a constant Péclet number. In addition, the equivalent one‐dimensional governing equations for the concentrations of species in the tube and the permeable porous medium under the influence of CF are obtained. The proposed model is compared and verified with several existing models in the literature. Abstract : Conduits surrounded by permeable porous media are common in many natural and engineered dual‐porosity and dual‐permeability systems. The transfer of a neutral nonreacting mass species in a capillary tube with a permeable porous wall was studied under the influence of combined pressure‐driven and electro‐osmotic flows or simply combined flows.